Intracerebroventricular administration of the thyroid hormone analog TRIAC increases its brain content in the absence of MCT8 - Bárez-López, Soledad (PLoS One, 2019)
Patients lacking the thyroid hormone (TH) transporter MCT8 present abnormal serum levels of TH: low thyroxine and high triiodothyronine. They also have severe neurodevelopmental defects resulting from cerebral hypothyroidism, most likely due to impaired TH transport across the brain barriers. The use of TH analogs, such as triiodothyroacetic acid (TRIAC), that can potentially access the brain in the absence of MCT8 and restore at least a subset of cerebral TH actions could improve the neurological defects in these patients. We hypothesized that direct administration of TRIAC into the brain by intracerebroventricular delivery to mice lacking MCT8 could bypass the restriction at the brain barriers and mediate TH action without causing hypermetabolism. We found that intracerebroventricular administration of therapeutic doses of TRIAC does not increase further plasma triiodothyronine or further decrease plasma thyroxine levels and does not alter TH content in the cerebral cortex. Although TRIAC content increased in the brain, it did not induce TH-mediated actions on selected target genes. Our data suggest that intracerebroventricular delivery of TRIAC has the ability to target the brain in the absence of MCT8 and should be further investigated to address its potential therapeutic use in MCT8 deficiency.